An Integrated Continuous‐Flow Synthesis of a Key Oxazolidine Intermediate to Noroxymorphone from Naturally Occurring Opioids. Issue 44 (14th August 2017) - Mata, Alejandro; Cantillo, David; Kappe, C. Oliver
Abstract : A telescoped procedure for the direct preparation of an advanced intermediate towards noroxymorphone from the naturally occurring alkaloids oripavine and thebaine is presented. The reaction procedure involves an intensified continuous‐flow hydroxylation, followed by a continuous solvent switch and hydrogenation in a packed‐bed hydrogenator (H‐Cube). The obtained reaction mixture, containing oxymorphone as intermediate in excellent yield and purity, can be then directly converted into the desired noroxymorphone oxazolidine intermediate through palladium catalyzed N ‐methyl oxidation. Abstract : From poppy towards active pharmaceutical ingredients: A telescoped continuous‐flow procedure for the preparation of an advanced intermediate for the synthesis of various opioid antagonists from oripavine and thebaine is presented.